Management Information System Innovation in Developing the Quality of Educational Services at the Amanatullah Islamic Boarding School in Banyuwangi - Istikomah Istikomah; Mufidah Cholil; Khotimatus Solikhah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This research, entitled